Odpowiedzi

2009-12-01T22:45:39+01:00
A) -6y+9x+6y+4x= 9x+4x = 13x
b) -4x+20y+6y+3x= -1x+26y
c) 3x+4y-3x-x-y= -x+3y
e) 4x+4y -2x+2y-3x-3x-y= x+5y
f) -10x+5xy-5xy-y-10xy+10x= -y-10xy
d) -xz+xy+xz-yz= xy-yz
2009-12-01T22:54:20+01:00
A) -3(2y-3x)+2(3y+2x)
-6y+9x+6y+4x
13x
b) -4(x-5y)-3(-2y-x)
-4x+20y+6y+3x
-x+26y
c) 2x(x+2y)-x(2x+y)
2x²+4xy-2x²-xy
3xy
d) -x(z-y)-z(-x+y)
-xz+xy+xz-yz
xy-yz
e) 4(x+y)-2(x-y)-3x(1+y)
4x+4y-2x+2y-3x-3xy
-x+6y-3xy
f) -5x(2-y)-y(5x+1)+10x(-y+1)
-10x+5xy-5xy-y-10xy+10x
-y-10xy
2009-12-01T23:03:06+01:00
A) -3( 2y -3x) +2 (3y +2x) =-6y+9x +6y+4x =13x B)-4(x-5y)-3(-2y-x) =-4x+20y+6y+3x=-1x+26y c)2x(x+2y)-x(2x+y)=2x²+4xy-2x²-xy=3xy d)-x(z-y)-z(-x+y)=-xz+xy+zx-zy=xy-zy e)4(x+y)-2(x-y)-3x(1+y)=4x+4y-2x+2y-3x-3xy=-1x+6y-3xy f)-5x(2-y)-y(5x+1)+10x(-y+1) =-10x+5xy-5xy-y-10xy+10x=-y-10xy